A Series of Strategic Cooperation Towards 100 Years of In-donesia-France Relations - A. Junaedi Karso (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Macron's visit also commemorated 75 years of diplomatic relations and a decade of strategic partnership between Indonesia and France. This meeting showed how bilateral diplomacy can trigger long-term transformation in various sectors. The partnership is part of extending the diplomatic relations between the two countries, which will be 100 years old in 2050. Indonesia and France are developing strategic partnerships in various important sectors, ranging from defense, technology, agriculture, economy, to culture. Both countries have the same vision of world order. The strategic partnership strengthens their positions in facing global uncertainty with a total of 21 strategic agreements. The forms of cooperation and strategic agreements between Indonesia and France include: 1) Defense sector, for example, the Indonesian Ministry of Defense and the French Ministry of Armed Forces agreed to establish a strategic partnership related to the exchange and joint protection of confidential information in the defense sector, 2) Economic sector, both countries agreed to encourage more balanced trade and investment relations, including: (1). MoU between the National Nutrition Agency and Danone; (2). Danantara and Eramet; (3). Investment Agreement between PT RGE Indonesia and Total Energies; (4). Investment Agreement between PT Citra Bonang Indonesia and Lesaffre; (5). MoU between PT SMI, PT PLN, and HDF; (6). MoU between Bank Indonesia and Banque De France, 3) Indonesia and France agreed to encourage Palestinian independence. This is considered the only way to resolve the long conflict between Palestine and Israel. Humanity must be prioritized in order to realize peace in the region. Two State Solutions